The impact of competencies on employability in Poland - Topolewska, Kamila (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Employee competencies are some of the most important elements of human resources management. Their value is clear even at an early stage of an employee selecting process because the hiring of a qualified employee can significantly reduce the costs related to training. Although the remuneration of qualified workers is usually higher, there is one key balancing aspect at play here, namely the fact that high level of knowledge and skills of a team allows for easier adaptation to changing market conditions. These competencies also have a similar value in case of other processes, such as: assessment, motivation, and employee development. Thus, considering their importance, it seemed worthwhile to analyse the impact of competencies on employability, both from the point of view of an organization and the labor market. Aim: The aim of the work is to determine the impact of individual characteristics and professional competencies on the likelihood of employment. Results: Based on the logit model estimates, it might be concluded that the following factors have the greatest positive impact on employability: age 41–50, having a driving license, higher education, readiness to work unusual hours required by the employer, and the ability to operate machines, tools and technical devices. The features that adversely affect the employability of the surveyed individuals include: lack of readiness to work unusual hours required by the employer, female gender, and lack of the ability to analyse information and draw conclusions.